Semiconducting M2X (M = Cu, Ag, Au; X = S, Se, Te) monolayers: A broad range of band gaps and high carrier mobilities - Gao, Lei; Zhang, Yan-Fang; Du, Shixuan (Nano research, 2021)
Two-dimensional semiconductors (2DSCs) with appropriate band gaps and high mobilities are highly desired for future-generation electronic and optoelectronic applications. Here, using first-principles calculations, we report a novel class of 2DSCs, group-11-chalcogenide monolayers (M 2 X, M = Cu, Ag, Au; X = S, Se, Te), featuring with a broad range of energy band gaps and high carrier mobilities. Their energy band gaps extend from 0.49 to 3.76 eV at a hybrid density functional level, covering from ultraviolet-A, visible light to near-infrared region, which are crucial for broadband photoresponse. Significantly, the calculated room-temperature carrier mobilities of the M 2 X monolayers are as high as thousands of cm 2 ·V −1 ·s −1 . Particularly, the carrier mobilities of η-Au 2 Se and ε-Au 2 Te are up to 10 4 cm 2 ·V −1 ·s −1 , which is very attracitive for electronic devices. Benefitting from the broad range of energy band gaps and superior carrier mobilities, the group-11-chalcogenide M 2 X monolayers are promising candidates for future-generation nanoelectronics and optoelectronics.